Nicotine Poisoning Trends in Georgia - Oluwayomi Fabayo; Alina Chung; Ray Kenneth; Jean O'Connor (Journal of the Georgia Public Health Association, 2016)
Background: Nicotine is a toxic chemical that can cause adverse health effects. Nicotine poisoning can result from exposure to tobacco and other nicotine containing products. It can cause nausea, vomiting, abdominal pain, fever, dizziness, seizures, tachycardia, hypertension and edema. Nicotine poisoning can affect both adults and children. Methods: The Georgia Department of Public Health secured data from the Georgia Poison Center in order to analyze nicotinespecific poisoning calls, including e-cigarette poisoning calls. The data on tobacco/nicotine poisoning or exposure calls were collected from April 2009 to April 2015. The data on calls related to nicotine poisoning from e-cigarettes were collected from January 2011 to April 2015. Results: Approximately 1,513 tobacco/nicotine poisoning calls were received over 6 years. Of these, 1, 212 were related to exposures in children ages 0 to 5 years, including 853 from cigarette use, 474 from cigars and chewing tobacco, and 23 from Nicoderm, Nicorette and hookahs. Approximately, 164 calls on nicotine poisoning from e-cigarettes were received over 4 years. Of these, 93 were related to exposure in children ages 0 to 5 years. Ingestion accounted for 107 of the calls, while 22 had nicotine poisoning through dermal routes, 21 through inhalation/nasal routes and 12 through ocular routes. Conclusions: Nicotine poisoning is a major public health problem in Georgia; it is caused by tobacco products and electronic nicotine delivery systems. Adopting tobacco-free/smoke-free policies that include e-cigarettes in homes, workplaces and vehicles will prevent nicotine poisoning.